Tuning of type-I and type-II mechanisms for visible light degradation in tris(styryl)benzene-sensitized TiO2 nanoparticles. (January 2021) - Ortiz-Bustos, Josefa; Hierro, Isabel del; Sánchez-Ruiz, Antonio; García-Martínez, Joaquín C.; Pérez, Yolanda
Abstract: The visible light activation of TiO2 have been carried out by sensitization method using robust and metal-free tris(styryl)benzene (TSB) compounds as efficient sensitizers, which can be easily prepared. TSB compounds decorated with three carboxylic acid (3 COOH ) or aldehyde (3 CHO ) groups have been tightly incorporated to the surface of TiO2 nanoparticles through different chemical linkage. The synthesized materials have been deeply characterized by different spectroscopic and analytical techniques to investigate the effect of TSB sensitizers in the photocatalytic properties of TiO2 . Comparative and exhaustive optical studies have been performed in solution between TSB compunds and sensitized TiO2 nanoparticles, computational studies have been also carried to shed light on the sensitization process. The results reveal different mechanisms of sensitization (Type I and Type II) between the 3 CHO and 3 COOH compounds and TiO2 nanoparticles. Thus, the influence of electronic injection mechanism (direct or indirect) has been studied and mechanisms have been proposed for photodegradation of dye pollutants under UV and visible irradiation. TiO2 nanoparticles sensitized with 3 COOH (TiO 2 –3 COOH ) exhibited the best visible photocatalytic activity with a removal efficiency around 98% for methylene blue in 30 min and methyl orange after 60 min. Graphical abstract: Direct electron injection mechanism of sensitization of TiO2 nanoparticles has shown to be the most efficient strategy for enhancing UV and visible photocatalytic activity in the degradation of dye pollutants. Image 1 Highlights: Sensitized TiO2 nanoparticles for photodegradation of dye pollutants. Optical and computational studies. The influence of electronic injection mechanism.